Born To Defend - Jet Li; Jet Li; Dean Harrington; Kurt Roland Petersson; Jia Song; Paulo Tocha; Erkang Zhao (HongKong MMII Passion Production, 1986)
Jet, a young soldier at the end of the second world war must overcome some abusive Americans who are bullying him as well as the Chinese people.
Language(s): Turkish, English Subtitle(s): Turkish
Keywords: Action; War